2016
DOI: 10.1111/jpn.12478
|View full text |Cite
|
Sign up to set email alerts
|

Different physical forms of one diet fed to growing pigs induce morphological changes in mandubular glands and local leptin (Ob) production and receptor (ObR) expression

Abstract: The physical form of the diet plays an important role for morphological adaptations of organs in the gastrointestinal tract. It was hypothesized that different physical forms of one diet could exert extra-enteric effects, under local and systemic neuroendocrine regulation. Gross morphology, fresh mass and cytoarchitecture of mandibular glands (MG) were studied in growing pigs fed with one diet processed under four different physical forms. Four dietary treatments were offered for 4 weeks to 32 growing pigs (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…All animals were housed individually without litter. For the specific dietary treatment, see Cappai et al., . All pigs were fed ad libitum with fresh diet every morning and had free access to water.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All animals were housed individually without litter. For the specific dietary treatment, see Cappai et al., . All pigs were fed ad libitum with fresh diet every morning and had free access to water.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Cappai et al. () reported morpho‐functional changes in the mandibular gland of growing pigs fed with different physical forms of the same diet. They showed that a coarser diet increased the expression of leptin and its receptor in the epithelial cells of striated ducts (Cappai et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent data in pigs indicated that molecular and morpho-function of mandibular gland of pigs may be influenced by physical form of diet. A coarser diet was shown to increase the expression of leptin and its receptor in the epithelial cells of striated ducts in growing pigs (93). Further studies in piglets demonstrated differential expression and localization of cannabinoid receptors type 1 (CB1) and cannabinoid receptors type 2 (CB2) in the mandibular glands in response to variable chewing activity due to different diets form (94).…”
Section: Appetite Control and Neuromodulationmentioning
confidence: 99%